Optimasi Pembelajaran Daring Berbasis LMS Untuk Meningkatkan Kinerja Akademik Mahasiswa Keperawatan - Juliati Koesrini; Tien Aminah (CV. Multi Kreasi Media, 2025)
The use of technology in higher education, particularly in the nursing field, is growing along with the adoption of online learning systems based on Learning Management Systems (LMS). However, ITSK RS dr. Soepraoen Malang faces problems related to the suboptimal use of LMS, including limitations in the use of LMS features, low student engagement in online learning, and limited technological skills among some lecturers and students. These problems have the potential to reduce the quality of learning and academic performance of nursing students. As a solution, this proposal aims to optimize the use of LMS at ITSK RS dr. Soepraoen Malang by providing training to lecturers and students, developing digital learning modules that can be accessed online, and introducing strategies to increase student engagement. Through this approach, it is hoped that the learning process will be more interactive, efficient, and engaging, thereby improving the motivation and learning outcomes of nursing students. The objectives of this community service are to improve the skills and understanding of LMS use by lecturers and students, optimize existing LMS features, and improve the academic performance of nursing students through more structured and interactive learning. It is hoped that the results of this community service will have a positive impact on the quality of technology-based nursing education.